Engineering maths - Mustoe, L. R. (Essential maths for students, 1997)
Engineering Maths uses an informal and user-friendly approach to provide first year engineering students with a solid mathematical base for their subsequent years of study. Essential topics are covered clearly and concisely and key ideas are highlighted and developed through detailed examples rather than formal proofs. Extensive exercises and self-assessment questions guide student understanding and help build the confidence to apply maths to the solution of engineering problems.